Ekstraksi Hidrotermal Senyawa Paradol dari Jahe - Priyono Kusumo; Mohammad Endy Yulianto; Andi Nur Alamsyah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Ginger contains a variety of active constituents. The active constituents of ginger are very diverse and varied.The diversity of the active constituents of ginger can depend on the type of ginger, ginger planting locationand circumstances of ginger (fresh or dried). One of the ginger active constituents that reported having somepharmacological activities is paradol. Several extraction methods have been carried out to obtain the activecompound of ginger, paradol. Hydrothermal extraction has gaining many interests from the researches due tothe unique properties of subcritical water used in the hydrothermal process. This research objective was tostudy the effect of extraction parameter process i.e. reaction temperature (1300C and 1400C) and time (10-40minutes). Hydrothermal extraction process carried out at a fix pressure of 2 bar. The research showed that thehydrothermal extraction process carried out at a fix pressure of 2 bar, a temperature of 1300C and extractiontime of 20 minutes was able to produce extracts with paradol content of 19%. The hydrothermal extractionprocess carried out at a temperature of 1300C, a pressure of 2 bar for 10 minutes can produce extractscontaining paradol of 16%, while the hydrothermal extraction process carried out at a temperature of 1300C,a pressure of 2 bar for 30 minutes is only able to produce extracts containing paradol of 6%.